Nanosecond‐laser application in intermediate AMD: 12‐month results of fundus appearance and macular function. (11th November 2013) - Guymer, Robyn H; Brassington, Kate H; Dimitrov, Peter; Makeyeva, Galina; Plunkett, Malcolm; Xia, Wie; Chauhan, Devinder; Vingrys, Algis; Luu, Chi D
Abstract Background A novel, ultra‐low energy nanosecond laser (retinal rejuvenation therapy) has been developed with the aim to slow progression of early age‐related macular degeneration (AMD). The safety, changes in fundus characteristics and macular function in a cohort of participants with bilateral intermediate AMD are reported. Design Prospective non‐randomised, pilot intervention study. Participants or Samples Subjects with bilateral intermediate AMD (n = 50, aged 50–75 years). Methods Ultra‐low energy laser pulses applied in 12 spots around the macula of one eye (0.15–0.45 mJ), using 400 μm diameter spot, 3 nanosecond pulse length, 532 nm wavelength and energy titrated to each patient. Main Outcome Measures Best corrected visual acuity, drusen area and macular sensitivity (flicker perimetry) at baseline and at 3, 6 and 12 months post‐laser. Results Treatment was painless with no clinically visible lesions. No participant developed choroidal neovascularization, while two with thin central retinal thickness at baseline developed atrophy at 12‐month follow up. Drusen area was reduced in 44% of treated eyes and 22% of untreated fellow eyes, with changes in drusen and function not being coincident. Improvement in flicker threshold within the central 3° was observed in both the treated and untreated fellow eyes at 3 months post‐laser. Of the 11 eyes at greatest risk of progression (flicker defect >15 dB), seven improved sufficiently to be taken out of this high‐risk category. Conclusions A single unilateral application of nanosecond laser to the macula produced bilateral improvements in macula appearance and function. The nanosecond retinal rejuvenation therapy laser warrants ongoing evaluation as an early intervention for AMD.